2019
DOI: 10.15666/aeer/1705_1263912647
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chicken Manure on Yield and Yield Criteria of Onion (Allium Cepa L.) as Second Crop

Abstract: This study was conducted to determine the residue effects of chicken manure on the yield and yield components of eight onion varieties as second crop after lettuce in field condition. Varieties (14-16, Burgaz, Karbeyazı, Naz, NWG, Perwana, Seyhan, Şampiyon) and also four different doses of chicken manure at the rates of 0, 20, 40, 60 t ha -1 with the recommended dose of NPK were used. A non-fertilized parcel was used as control. The experiment was laid out in split plot design and replicated three times. Yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Also, Mahala et al (2018) inducated that the positive effect of organic manure may be due to FYM help to increase the nutrients availability and improve physical and chemical properties. Yoldas et al (2019) and Al-Amri and Alabdaly (2021) reported similar results in their work.…”
Section: Onion Productivitysupporting
confidence: 74%
“…Also, Mahala et al (2018) inducated that the positive effect of organic manure may be due to FYM help to increase the nutrients availability and improve physical and chemical properties. Yoldas et al (2019) and Al-Amri and Alabdaly (2021) reported similar results in their work.…”
Section: Onion Productivitysupporting
confidence: 74%
“…The highest bulb yield (8.767 t/ha) and highest bulb diameter (3.787 cm) were obtained with Rovral treated plot. Antagonistic effect of poultry manure against other plant pathogen is also reported by several researchers (Meah, et al, 2004;Islam, 2005, Bhuiyan, 2010Hasanat, 2011;Yoldas et al, 2019). Poultry manure increases the microbial activity of soil borne antagonist that indirectly contributes for the management of the plant pathogens.…”
Section: Effect Of Different Treatments On Yield and Yield Contributi...mentioning
confidence: 53%
“…The studies discussed various aspects of onion production and fertilization methods. Yoldas et al (2019) highlighted the positive impact of poultry manure, indicating a significant increase in yield, especially with a 60 t/ha application. Mallanagouda et al (1995) found that the highest onion yield resulted from combining the recommended NPK amount with animal manure.…”
Section: Introductionmentioning
confidence: 99%